2013
DOI: 10.1177/2048872613481449
|View full text |Cite
|
Sign up to set email alerts
|

Interhospital transfer due to failed prehospital diagnosis for primary percutaneous coronary intervention: an observational study on incidence, predictors, and clinical impact

Abstract: Background: For patients with ST-elevation myocardial infarction (STEMI), guidelines recommend prehospital triage and direct referral to a percutaneous coronary intervention (PCI)-capable centre in order to minimize ischemic time. However, few have studied failed prehospital diagnosis. We assessed the incidence, predictors, and clinical impact of interhospital transfer for primary PCI after initial referral to a non-PCI-capable centre due to a failed prehospital STEMI diagnosis. Methods: We studied 846 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 24 publications
4
25
0
1
Order By: Relevance
“…The present study included only STEMI patients presenting in an emergency department with PCI facilities or else managed by MICU; cases involving interhospital transfer were excluded, to minimize bias. Thus the results do not show longer system delay for women, as previously reported, especially in terms of lower priority for MICU management 24 and higher rates of overlooked pre-hospital STEMI diagnosis 37 . The recent Swiss study observed, in of 4723 patients presented with acute MI, discrimination of elderly patients and females in the provision of pPCI 38 .…”
Section: Accepted Manuscriptsupporting
confidence: 74%
“…The present study included only STEMI patients presenting in an emergency department with PCI facilities or else managed by MICU; cases involving interhospital transfer were excluded, to minimize bias. Thus the results do not show longer system delay for women, as previously reported, especially in terms of lower priority for MICU management 24 and higher rates of overlooked pre-hospital STEMI diagnosis 37 . The recent Swiss study observed, in of 4723 patients presented with acute MI, discrimination of elderly patients and females in the provision of pPCI 38 .…”
Section: Accepted Manuscriptsupporting
confidence: 74%
“…These diagnoses constitute only a fraction of indications for inter-hospital transfers. Despite established practices, delays are frequent and often related to unnecessary testing, uncertain diagnoses, and imperfect adherence to guidelines[12, 23–26]. …”
Section: Introductionmentioning
confidence: 99%
“…Certainly, a short time to first medical contact is desirable to facilitate expeditious diagnosis and early pharmacological therapy and to treat possible life-threatening complications such as arrhythmia or cardiogenic shock. Second, while 12-lead ECG-based prehospital triage has shown to contribute to early diagnosis and treatment in STEMI patients [73,74], this is not the case in NSTEMI patients who also require (in-hospital) cardiac biomarker assessment for diagnosis [75]. Finally, whereas delay to reperfusion should be as short as possible to optimize outcome in STEMI patients [76], the relation between delay to reperfusion and outcome in NSTEMI is more complex.…”
Section: Delay To Reperfusion In Nstemimentioning
confidence: 94%